2006
DOI: 10.1212/01.wnl.0000194255.82542.6b
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality cues for improvement of gait in patients with multiple sclerosis

Abstract: Patients with multiple sclerosis showed improvement in walking abilities using virtual reality visual-feedback cues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(63 citation statements)
references
References 20 publications
0
61
0
2
Order By: Relevance
“…Hemiparetic stoke patients who performed a task-orientated exercise program under conditions of vision and surface manipulations showed more improvement in their standing balance than a control group that performed a conventional task-oriented program [25]. Patients with balance control problems [26][27][28] and gait disturbances [29,30] have also demonstrated improvement following adaptive generalization training. We believe analogous improvements might be made in the reduction of gait ataxia in returning astronauts if they are trained to make rapid adjustments to novel physical and sensory stimuli such as that produced by variations in visual flow and support surface stability.…”
Section: Discussionmentioning
confidence: 99%
“…Hemiparetic stoke patients who performed a task-orientated exercise program under conditions of vision and surface manipulations showed more improvement in their standing balance than a control group that performed a conventional task-oriented program [25]. Patients with balance control problems [26][27][28] and gait disturbances [29,30] have also demonstrated improvement following adaptive generalization training. We believe analogous improvements might be made in the reduction of gait ataxia in returning astronauts if they are trained to make rapid adjustments to novel physical and sensory stimuli such as that produced by variations in visual flow and support surface stability.…”
Section: Discussionmentioning
confidence: 99%
“…We sought to examine the effect of a wearable, closed-loop, visual-auditory cueing system on parkinsonian gait in the "off" state, when the magnitude of gait impairment is expected to be largest. Preliminary clinical studies [3,12] have demonstrated that the closed-loop feedback device significantly improves gait speed while in use and appears to induce a residual benefit for several days by dynamically delivering a tiled floor pattern adapted to the patient's own motion. It is believed that the optical flow provides a reassuring feedback effect, informing the patient of motion being performed and matching visual feedback from foot-tile matching to auditory feedback from clicking obtained for each step.…”
Section: Introductionmentioning
confidence: 99%
“…Although complete loss of sensation is rare, up to 80% of patients present with some sensory impairments, [1][2][3] and this is often the first sign of MS. Sensory loss can be a significant cause of disability, 4,5 and several studies have found that somatosensory impairments have a significant effect on gait 6,7 and balance 8,9 and lead to decreased mobility, independence, and quality of life 9,10 in people with MS.…”
mentioning
confidence: 99%